2010
DOI: 10.1080/07347332.2010.498459
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional Cancer Worry: Convergent, Divergent, and Predictive Validity of Existing Scales

Abstract: Objectives-Past research has suggested that dispositional cancer worry may be a key predictor of health behavior. The present study examined seven measures of dispositional cancer worry to see if they were significantly related (convergent validity), significantly different from similar but distinct traits (divergent validity), and capable of predicting cancer-relevant outcomes (predictive validity).Methods-489 undergraduate students completed a survey measuring dispositional worry, dispositional cancer worry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 40 publications
(46 reference statements)
4
47
0
Order By: Relevance
“…Jensen et al (2010) confirmed that cancer worry is a multidimensional construct consisting of severity and frequency. However, cancer worry-severity explained the greatest variance in cancer worry, and cancer worry-frequency within the general population is very low (Jensen et al, 2010). Thus, this study used the brief worry scale (Dijkstra & Brosschot, 2003) that measures cancer worry-severity.…”
Section: Participants and Proceduressupporting
confidence: 62%
See 1 more Smart Citation
“…Jensen et al (2010) confirmed that cancer worry is a multidimensional construct consisting of severity and frequency. However, cancer worry-severity explained the greatest variance in cancer worry, and cancer worry-frequency within the general population is very low (Jensen et al, 2010). Thus, this study used the brief worry scale (Dijkstra & Brosschot, 2003) that measures cancer worry-severity.…”
Section: Participants and Proceduressupporting
confidence: 62%
“…Cancer worry is a worry about an individual's own chance of developing cancer (Jensen, Bernat, Davis, & Yale, 2010). Many studies have investigated the relationship between cancer worry and cancer screening behaviors (Hay, Buckley, & Ostroff, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Valid and reliable measurement tools are essential to conducting grounded quantitative research (Chaffee, 1991;Jensen, Bernat, Davis, & Yale, 2010) and are especially needed to facilitate many areas of communication studies . The present study aimed to develop and validate a measure that addresses communication anxiety produced by having to speak in a foreign language in a medical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer worry can be distinguished from general anxiety (Jensen, Bernat, Davis, & Yale, 2010). It is correlated with perceived risk but also appears to have some independent origins (Jensen et al, 2010;Lipkus et al, 2000;R.…”
Section: Individual Determinants Of Cancer Screening Participationmentioning
confidence: 99%